Potential electricity savings by variable speed control of compressor for air conditioning systems - Nasution, Henry; Wan Hassan, Mat Nawi (Springer Berlin / Heidelberg, 2006)
The potential of a variable-speed compressor running on a controller to provide enhanced load-matching capability, energy saving and thermal comfort for application in air-conditioning system is demonstrated. An air-conditioning system, originally operated on a constant speed mode, is retrofitted with an inverter and a PID controller. The system was installed to a thermal environmental room together with a data acquisition system to monitor energy consumption and temperature of the room. Measurements were taken 2 h daily at a time interval of 5 min for an on/off and an inverter variable-speed conditions. The results indicate that thermal comfort of the room together with energy saving can be obtained through a proper selection of K for the controller. At a temperature setting of 22Â°C, the energy saving for the system is estimated to reach 25.3% for PID controllers.